Expression of Neurog1 instead of Atoh1 can partially rescue organ of Corti cell survival. - Israt Jahan (PLoS ONE, 2012)
In the mammalian inner ear neurosensory cell fate depends on three closely related transcription factors, Atoh1 for hair cells and Neurog1 and Neurod1 for neurons. We have previously shown that neuronal cell fate can be altered towards hair cell fate by eliminating Neurod1 mediated repression of Atoh1 expression in neurons. To test whether a similar plasticity is present in hair cell fate commitment, we have generated a knockin (KI) mouse line (Atoh1(KINeurog1)) in which Atoh1 is replaced by Neurog1. Expression of Neurog1 under Atoh1 promoter control alters the cellular gene expression pattern, differentiation and survival of hair cell precursors in both heterozygous (Atoh1(+/KINeurog1)) and homozygous (Atoh1(KINeurog1/KINeurog1)) KI mice. Homozygous KI mice develop patches of organ of Corti precursor cells that express Neurog1, Neurod1, several prosensory genes and neurotrophins. In addition, these patches of cells receive afferent and efferent processes. Some cells among these patches form multiple microvilli but no stereocilia. Importantly, Neurog1 expressing mutants differ from Atoh1 null mutants, as they have intermittent formation of organ of Corti-like patches, opposed to a complete 'flat epithelium' in the absence of Atoh1. In heterozygous KI mice co-expression of Atoh1 and Neurog1 results in change in fate and patterning of some hair cells and supporting cells in addition to the abnormal hair cell polarity in the later stages of development. This differs from haploinsufficiency of Atoh1 (Pax2cre; Atoh1(f/+)), indicating the effect of Neurog1 expression in developing hair cells. Our data suggest that Atoh1(KINeurog1) can provide some degree of functional support for survival of organ of Corti cells. In contrast to the previously demonstrated fate plasticity of neurons to differentiate as hair cells, hair cell precursors can be maintained for a limited time by Neurog1 but do not transdifferentiate as neurons.